All-Optical Two-Way Relaying Space Laser Communications for HAP-based Broadband Backhaul Networks - Vu, Minh Q. (2019)
High-altitude platforms (HAPs), which are innovative systems for next-generation wireless communication systems, are being researched and developed rapidly . The HAPs combine the advantages of both satellite communication systems and terrestrial free space optical (FSO) link. In this research, we propose an all-optical two-way relaying space laser communication system for HAP-based broadband backhaul networks to increase the coverage area and to cope with unexpected disasters which occur between two terminals. We also applied network coding scheme for our proposed system by using an optical XOR gate at HAP to increase security and have the faster speed of processing than an electrical one. The numerical results of our proposed system’s performance are exhibited to prove the feasibility of ours